Psychological characteristics of innovativeness - Bartolome, Claribel D.
This study investigated the relationship of certain personality and intellectual variables to creativity/innovativeness of Filipino youths in various fields. Personality differences do exist among innovatives across fields especially with respect to the following dimensions: thoughtfulness, orderliness, creativity, risk-taking, sensitiveness, obedience, intelligence, and patience. The result of this study indicate that society in general and schools in particular should never discourage innovativeness by putting too much emphasis on conformity and punishment for deviation in the form of reprimand, isolation, or exclusion.
Originally presented as the author's thesis; University of the Philippines, 1990.
Keywords: Personality and intelligence; Educational innovations -- Psychological aspects; Personality and creative ability